Molecular engineering of biomolecule-based functional nanodots for biomedical applications - Xu Victor Hesheng (Nanyang Technological University, 2020)
In recent years, nanotechnology has gained considerable attention owing to its numerous attractive properties. Bestowed with quantum mechanical effects, nanomaterials exhibit unique properties including high surface-to-volume ratio, great strength and ductility, ease of functionalization and enhanced cargo loadings. This enabled great versatility in their application, especially in the field of biomedicine. Nonetheless, the preparation of these nanomaterials is often challenging, involving tedious multistep synthesis and expensive reagents. In addition, the fabrication usually utilises harsh and toxic reagents which are hazardous towards human and environmental health. Consequently, this restricts the effectiveness of their applications. Unlike the conventional synthesis, bioinspired synthesis represents new facile and benign strategy for the fabrication of nanomaterials. This strategy offers a simple and green approach as it utilises mainly biomolecules ranging from macro biostructures such as protein, DNA, to poly saccharides, polypeptide and even the building units such as nucleotides and amino acid, and their intrinsic properties to facilitate the formation of nanomaterials. Moreover, the resulting bioinspired nanomaterials are often endowed with unique characteristics such as rich chemical functionalities, aqueous solubility, unusual optical features, and great biocompatibility. Besides, through careful selection of the biomolecule precursors, the resulting nanomaterials can be engineered with desired morphology and properties. Hence, this strategy creates a new programmable assembly of nanomaterials with multifunctional properties which enabled great versatility in their application, especially in the field of biomedicine. In this thesis, bioinspired synthesis strategy was employed to prepare various unique biodots. The biodots were developed through critical combinations of mainly amino acid, Serine, and carefully selected precursors such as PEI (polyethylenimine) and histamine. The resulting biodot (ie. Ser-dot, Ser-PEI biodot and Ser-Hist biodot) displayed enhanced properties which is suitable for applications including bioimaging, antibacterial therapy and biosensing respectively. These findings could provide essential insights towards interaction of the biomolecular precursors and the formation of the biodot, thus, potentially improving understanding towards more responsive and multifunctional nanostructure for complex applications such as theranostic, deep tissue diagnosis and nanorobots for surgery.